The Road to the White House : The Politics of Presidential Elections - Wayne, Stephen J. (London Macmillan Press, 1984)
A behind-the-scenes guide to the strategy and tactics for being elected the American President.
Include Index and Appendix
Keywords: Presidents--Election -- United States